LA NAKKA DALAM BINGKAI PEMBANGUNAN KABUPATEN BARRU 1960-1965 - Muhammad Zainuddin Badollahi; Hilda Anjarsari; Intan Lisu Tandungan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2019)
This study focused on the governance of La Nakka the period from 1960 to 1965. Here the author reveals how the conditions of Barru was when La Nakka be the first district of Barru amid an unstable condition because of the political turmoil. The purpose of this study was to determine the condition of the reign Barru La Nakka ,while also knowing any reaction arising among local authorities when Barru changes from the autonomous areas into District level II . Additionally seen what policies will also be issued during his reign . This research method is the collection of resources , verification , interpretation and writing. The results of this study found that as the first Regent in Barru, La Nakka managed to build an independent district in agriculture, education and transportation. The opening of the road that connects Pekkae Soppeng with Barru one proof of its success. Besides La Nakka too many schools for the advancement of education in Barru.